Cloning and expression of T4 DNA polymerase. - Lin, T C (1987)
The structural gene coding for bacteriophage T4 DNA polymerase (gene 43) has been cloned into inducible plasmid vectors, which provide a source for obtaining large amounts of this enzyme after induction. The T4 DNA polymerase produced in this fashion was purified by an innovative three-step procedure and was fully active.